Sale of the business of the year ISAGEN (2014)
This essay collects information from the third generator and distributor of electricity in Colombia ISAGEN, its projection of growth abroad , in search of a strategic partner with extensive experience in the sector and financial muscle that it is competitive and agile decisions meet the challenges it will bring the growing demand for electricity in Colombia, with the expectation that no short-term business with this properties for sale in Colombia or Latin America, the analysis be undertaken from two perspectives in corresponding to the viewpoint of ISAGEN, history and challenges and the other corresponds to the standpoint of government on the initiative of sale in order to finance other assets, this is the infrastructure, which is missing in the nation to be more competitive with the TLC analysis of the pro and against ISAGEN sale will be made, and whether to change an asset for others a productive asset will be in production, if new investment as the rate of ROI, finally present three possible outlets for selling ISAGEN not, as in this work not discussed the need to strengthen the infrastructure of road maya or helps fund the investments described in the highway concession program fourth generation.